2007
DOI: 10.1097/hjr.0b013e32828622d7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on the glutathione antioxidant system

Abstract: This study represents the first longitudinal investigation involving the effects of multiple modes of exercise training on the GSH antioxidant system with evidence, suggesting the GHS:GSSG ratio as the most sensitive change marker. The significant findings of this study have potential clinical implications to individuals involved in cardiac and pulmonary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 43 publications
6
48
1
1
Order By: Relevance
“…In sedentary, able-bodied individuals, a 6-week exercise program resulted in a significant increase in resting glutathione and decrease in glutathione disulfide levels compared with a control (no exercise) group. 89 Similar findings of decreased oxidative stress, accompanied by improvements in aerobic fitness with long-term (up to 12 months) exercise training were found among a group of previously sedentary older adults. 90,91 However, improvements in antioxidant capacity are also readily reversed by detraining (e.g.…”
Section: Oxidative Stress and Rehabilitation In Chronic Scisupporting
confidence: 57%
“…In sedentary, able-bodied individuals, a 6-week exercise program resulted in a significant increase in resting glutathione and decrease in glutathione disulfide levels compared with a control (no exercise) group. 89 Similar findings of decreased oxidative stress, accompanied by improvements in aerobic fitness with long-term (up to 12 months) exercise training were found among a group of previously sedentary older adults. 90,91 However, improvements in antioxidant capacity are also readily reversed by detraining (e.g.…”
Section: Oxidative Stress and Rehabilitation In Chronic Scisupporting
confidence: 57%
“…This has been shown in healthy populations [18] . The combination of aerobic exercise and strength training has been shown to be optimal for increasing GSH in the obese and in healthy older adults [19,20] .…”
Section: Introductionsupporting
confidence: 57%
“…A power analysis was performed based upon previous work by Elokda and Nielsen [18] . A sample size of 28 subjects in total (7 per group) was calculated to provide a 95% power to detect a difference in the mean change of GSH at 100 M .…”
Section: Design and Sample Size Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor contributing to the rise in plasma FORD is the tri-peptide glutathione (GSH; (Palmieri and Sblendorio 2007). Several studies in elite athletes have reported acute and chronic changes in blood GSH in response to exercise (Lewis et al 2015), with exercise training known to elicit the up-regulation of intra-cellular GSH (Elokda and Nielsen 2007), and intra-cellular GSH being a significant source of blood GSH (Giustarini et al 2008). Thus plasma changes in the athletes FORD values may largely reflect changes in vitamin C and GSH; this was not tested experimentally in the present study.…”
Section: Discussionmentioning
confidence: 88%